Negro drama : reflexões sobre o impacto do racismo ambiental no genocídio de jovens negros em Rondonópolis-MT - Teixeira, Felipe Barbosa (2020)
The paper presents a discussion on environmental racism and its impact on black youth in Rondonópolis-MT through bibliographic reviews of works about racism in Brazil, online public documentation and municipal physical files on the policies given to the population in Rondonópolis-MT. The research that supports this dissertation started from a dialogue with authors on the theme in question, from observation and analysis of statistical data, public domain documents, which deal with thinking, among other things, about the theme of environmental racism. Branquitude's main strategy is to blame blacks for their own situation, since being privileged whites, for not carrying the stigma of color and the burden of social disruption, they are exempt from responsibility for racial problems. In RondonópolisMT, statistical data shows that black students have a school dropout rate two and a half times higher than that of young white people, being still the main group to suffer from the high unemployment and unemployment rates in the city. In dialogue with the works of Abdias do Nascimento, Sueli Carneiro, Gevanilda Santos, Achille Mbembe, among other authors, it became evident that the genocide of young blacks is not only a local reality, but an ongoing, ongoing policy. On the other hand, we found that there is an evident relationship between the deschooling of young blacks, structural unemployment and the depletion due to hyperspecialization of the workforce, resulting from the allocation of black people in unstructured peripheries, not prepared for the reception and accommodation of people. It became evident that there are no deals interested in solving the problem of blacks, in combating situations characteristic of environmental racism in Rondonópolis-MT, and it is demarcated that power relations tolerate blacks from their most basic rights, criminalizing them by the situation of poverty in who lives, even though it was planned by a state and white elite that insists on not recognizing its privileges.